Compliance Dynamics Generated by Social Interaction Rules - Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study compliance dynamics generated by a large set of behavioral rules describing social interaction in a population of agents facing an enforcement authority. When the authority adjusts the auditing probability every period, cycling in cheating-auditing occurs: Intensive monitoring induces compliance, but with high compliance there is incentive for lax monitoring; with less monitoring, compliance starts decreasing, and then there is an incentive to intensify monitoring. Thus, the real life phenomenon of compliance fluctuations is ex-plained by the nature of social interaction process rather than by exogenous parameter shifts. For the authority committed to a fixed auditing probability, we derive a sufficient condition for fines to be effective means of deterrence. Our analysis can be applied, among others, to crime, tax evasion, safety regulations, employment and environmental protection.
Keywords: C79; D83; H26; K42; 330; social interaction; compliance; random matching; behavioral rule; learning